(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article outlined the scale of the COVID-19 pandemic in Ukraine and the world, which exacerbated the need to develop an effective system of quarantine and anti-epidemic measures. The social, political and legal nature of quarantine and anti-epidemic measures and their impact on the observance of certain rights and freedoms of citizens were considered. The purpose and direction of the system of quarantine and anti-epidemic measures were outlined. The following features of quarantine and anti-epidemic measures in the conditions of the COVID-19 pandemic were studied, such as a special procedure for introducing them into effect; their constant variability, adaptability in view of existing threats; the coronavirus in Ukraine to a certain extent contributed to the development of new areas of theoretical support and the development of a new type of public relations during the pandemic; the leading role of the police in ensuring quarantine and anti-epidemic measures in the conditions of the COVID-19 pandemic.